2021
DOI: 10.1017/jfm.2021.148
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning and accurate solutions of Reynolds average Navier–Stokes equations with data-driven turbulence closures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 58 publications
(179 reference statements)
3
22
0
Order By: Relevance
“…Although prior assessments show that the discrepancy between ML predictions and high-fidelity data is pretty small, other derived flow variables of ultimate interest, such as velocity and pressure, are possibly far removed from the true values for flows with higher Reynolds numbers. Recently, a few studies 46,47 showed that embedding ML prediction, i.e. the Reynolds stress field, explicitly into RANS equations would inevitably result in the lack of accuracy of data-driven turbulence models.…”
Section: Dsr For Turbulence Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior assessments show that the discrepancy between ML predictions and high-fidelity data is pretty small, other derived flow variables of ultimate interest, such as velocity and pressure, are possibly far removed from the true values for flows with higher Reynolds numbers. Recently, a few studies 46,47 showed that embedding ML prediction, i.e. the Reynolds stress field, explicitly into RANS equations would inevitably result in the lack of accuracy of data-driven turbulence models.…”
Section: Dsr For Turbulence Model Developmentmentioning
confidence: 99%
“…To avoid being ill-conditioned, it is necessary to decompose the Reynolds stress before it is injected into RANS simulations, as is done herein. This strategy has been proven to be effective in improving the stability and accuracy of data-driven RANS simulations 19,46,47 .…”
Section: Dsr For Turbulence Model Developmentmentioning
confidence: 99%
“…where iM u  is the fluctuation velocity and iM u  is the average velocity. When combining the equation above and N-S equations, we can obtain the Reynolds equation [25].…”
Section: Basic Mathematical Model Of Flowfield Letmentioning
confidence: 99%
“…2019 b ; Brener et al. 2021). Such ill-conditioning is particularly prominent in high-Reynolds-number flows; even an apparently simple flow such as a plane channel flow can be extremely ill-conditioned (Wu et al.…”
Section: Introductionmentioning
confidence: 99%